Effects of green manure intercropping on soil nutrient content and bacterial community structure in litchi orchards in China - Yuan, Bingchen; Yu, Daogeng; Hu, An; Wang, Yanru; Sun, Yuting; Li, Chengzhen (Frontiers in Environmental Science, 2023)
Green manure intercropping is an agronomic management practice that effectively increases soil nutrients in understory and reduces weed population. However, the influence of different green manures on soil properties and soil bacterial community in litchi orchards in the tropical regions of China remains largely unknown. Here, we examined the effect of intercropping three leguminous green manure crops in litchi orchards of Hainan Province. No intercropping was used as the control. Different green manures increased the contents of different soil nutrients. For example, Desmodium ovalifolium increased the total nitrogen content by 7.93%; Grona heterocarpos increased the ammonium nitrogen content by 558.85%; and Stylosanthes guianensis increased the available phosphorus content by 1207.34%. However, intercropping with D. ovalifoliu and S. guianensis reduced the content of available potassium by 47.29% and 58.48%, respectively. The intercropping of green manure increased the abundance of several microbial genera, including Bradyrhizobium, Serratia, and Bacillus, which are known to facilitate soil nitrogen accumulation, plant growth, and phosphorus dissolution. Compared with no intercropping, the three intercropping treatments significantly improved the contents of soil ammonium nitrogen and soil available phosphorus in the litchi orchard. Therefore, intercropping with green manure crops in litchi orchards is an effective management measure; however, the choice of the green manure crop should be based on the soil conditions of litchi orchards.